A novel murine model of LITT for glioblastoma reveals tumor reduction, BBB permeabilization, and drug delivery via ThermoDox® - Prazwal Athukuri; Karina Moreno; Malcolm F. McDonald; Ashley Puentes; Alfred Dei-Ampeh; Anantha Marisetty; Yuhui Yang; Sungho Lee; Khatri Latha; David Needham; Ganesh Rao (Drug Delivery and Translational Research, 2026)

Dynamics and Eco‐Genomics of Baltic Sea Nitrifiers: Seasonality, Niches, Interactions and Genomic Uniqueness - Sukki Sookyoung Kim; Elisa D'Agostino; David M. Needham (Environmental Microbiology, 2026)
Nitrification is widespread across marine systems, yet the ecological and evolutionary drivers shaping nitrifier populations remain largely unknown. The Baltic Sea, a brackish basin with pronounced gradients in salinity, oxygen, nutrients and strong seasonality, is a valuable model environment to investigate these questions. Here, we combined metagenomics and rRNA gene sequencing to characterise the spatiotemporal dynamics and genomic diversity of nitrifiers, alongside physicochemical measurements. Nitrifiers were persistently abundant throughout aphotic waters, with vertical niche partitioning and seasonal peaks in surface waters from late fall to early spring. The seasonal peaks were positively correlated with nitrite, nitrate and diverse other prokaryotes, and negatively correlated with solar radiation and chlorophyll. To probe the genomic basis of these ecological patterns of the numerically dominant nitrifier, we recovered five novel genomes of ammonia‐oxidising archaea through metagenomics of bulk samples and selective enrichments, including the dominant taxon from aphotic depths. Comparative genomics showed high gene conservation, with variation largely in genes linked to interactions with the external environment and nitrogen and phosphorus metabolism between central surface and deep types. Together, our study provides insights into niches of Baltic Sea nitrifiers and begins the process of understanding the mechanisms and functional implications of these patterns.

Identifying and addressing the components of extreme physical-oceanographical events for improved risk management in coastal systems - Eric P. Achterberg; Fabian Rackelmann; Ananya Ramesh; Jack O’Connor; Ovidio García-Oliva; Saranya Jayachandran; Viktoria Wichert; Xiangyu Li; Kaveh Purkiani; David M. Needham; Ingeborg Bussmann; Philipp Fischer; et al. (Frontiers in Marine Science, 2025)
Extreme physical-oceanographic events, such as marine heatwaves, fluvial floods, droughts and storm surges, have major impacts on local communities, economic sectors and ecosystems, and their frequency, intensity and duration increase due to climate change. There is a lack of understanding of the systemic drivers of extreme events as well as of their interconnected impacts on estuarine and coastal ecosystems. This knowledge is essential for assessing future impacts on ecosystem services and the local communities that depend on them, and to inform robust risk assessments and develop comprehensive risk management and adaptation strategies including early warning systems. Considering this, the German Alliance for Marine Research (DAM)-funded programme “ElbeXtreme” focuses on an integrated approach utilizing stakeholder engagement, data mining, experimental and field observations to develop novel observational and modelling approaches for assessing and monitoring risks in the Elbe estuary. The programme will deliver new insights into risks and impacts of extreme events in the estuarine system of the Elbe and the adjacent region of the North Sea (German Bight) to build a systemic risk understanding and support adaptation planning for local communities and ecosystems. Here we outline the rationale of the ElbeXtreme project and its planned activities, with the aim of stimulating national and international collaboration in tackling the urgent issue of marine and coastal risks.

Differentiation grade is highly concordant between matched primary and metastatic colorectal cancer - Camilla M. Reehorst; Jennifer K. Mooi; Charles J. Uy; Kristen A. Needham; Sarah Ellis; Ian Y. Luk; Laura J. Jenkins; Rebecca Nightingale; Fiona Chionh; Andreas Behren; Niall C. Tebbutt; David S. Williams; et al. (Clinical & Experimental Metastasis, 2025)
Differentiation grade of colorectal cancers (CRC) is histologically defined by the proportion of the tumour which retains the glandular architecture of the normal colon. Poorly differentiated CRCs display loss of glandular architecture and canonical markers of colonic differentiation and are associated with increased metastatic capacity and poorer prognosis. It is currently unclear whether poorly differentiated cells within a heterogeneous primary tumour are more likely to establish metastases and if this cellular trait is conserved in the secondary tumours, or whether metastasis is largely stochastic, with most cells in the primary tumour harboring metastatic potential. To explore this, we examined the concordance in histological grade, expression of markers of colonic differentiation, and epithelial to mesenchymal transition (EMT) in 67 matched primary and metastatic CRCs. Tumour differentiation grade was scored categorically, and expression of differentiation and EMT markers were scored as continuous variables. In matched primary-metastatic pairs, tumour grade was concordant in 88% of cases (59/67 pairs), irrespective of the site of metastasis. In tumour pairs with discordant grade (n = 8), tumour grade was higher in the metastatic lesion in 6/8 (75%) cases. Consistent with the histological concordance, expression of the key driver of colonic differentiation (CDX2); colonic lineage-specific markers (VIL1, MUC2, SYN and CHG); and the markers of epithelial-to-mesenchymal transition (E-Cadherin and Vimentin) were highly concordant between matched primary and metastatic lesions. Finally, no staining of the squamous lineage marker Cytokeratin5/6 was observed in either primary or metastatic tumours. Tumour grade assessed histologically or using expression of markers of colonic differentiation or epithelial to mesenchymal transition was largely concordant between primary and metastatic CRC. These findings complement previously reported genomic similarities between primary and metastatic lesions and demonstrate that the histological grade of a primary tumour can in most cases inform the differentiation grade of associated metastatic lesions.

Sex-specific associations between per- and polyfluoroalkyl substance exposure and epigenetic age: Findings from the National Health and Nutrition Examination survey 1999–2000 - Dennis Khodasevich; Anne K. Bozack; Belinda L. Needham; David H. Rehkopf; Andres Cardenas (Environmental Research, 2025)

Sensory impairments and epigenetic aging: insights from self-rated hearing and vision in United States adults - Jamaji C. Nwanaji-Enwerem; Dennis Khodasevich; Nicole Gladish; Hanyang Shen; Anne K. Bozack; Saher Daredia; Belinda L. Needham; David H. Rehkopf; Andres Cardenas (GeroScience, 2025)
Sensory impairments are common with aging, but studies examining the relationships of these impairments with DNA methylation–based biomarkers of aging, strong predictors of morbidity and mortality, remain sparse. We investigated whether subjective measures of sensory impairment are associated with epigenetic age biomarkers. We conducted a cross-sectional analysis in a representative sample of 2344 U.S. adults from the 1999–2000 and 2001–2002 cycles of the National Health and Nutrition Examination Survey (NHANES). We examined the relationships of self-rated auditory and vision function with seven epigenetic aging biomarkers: HannumAge, HorvathAge, SkinBloodAge, PhenoAge, GrimAge2, DNA methylation telomere length, and DunedinPoAm. We adjusted for potential confounders including chronological age, other demographics, lifestyle factors, and general health. In adjusted survey-weighted models, self-reported deafness was associated with a significantly higher GrimAge2 ( β = 4.19-years, 95% CI 2.29, 6.09, P = 0.004) and DunedinPoAm ( β = 0.07, 95% CI 0.04, 0.09, P = 0.002) compared to good hearing. Deafness was also associated with significantly higher GrimAge2 estimates of TIMP1 ( β = 459.51, 95% CI 287.00, 632.03 P = 0.002) and marginally higher estimated levels of ADM ( β = 10.06, 95% CI 1.76, 18.36, P = 0.03), CRP ( β = 0.34, 95% CI 0.11, 0.56, P = 0.01), and cigarette pack-years ( β = 6.55, 95% CI 2.62, 10.47, P = 0.01). No associations were observed with self-rated vision. We describe associations of self-rated deafness with accelerated epigenetic aging, as measured by GrimAge2 and DunedinPoAm. These results provide a foundation for future research exploring epigenetic biomarkers as tools for predicting and understanding the biological processes underlying sensory impairments like deafness.

Tree crown damage and its effects on forest carbon cycling in a tropical forest - Jessica F. Needham; Gabriel Arellano; Stuart J. Davies; Rosie A. Fisher; Valerie Hammer; Ryan G. Knox; David Mitre; Helene C. Muller‐Landau; Daniel Zuleta; Charlie D. Koven (Global Change Biology, 2022)
Crown damage can account for over 23% of canopy biomass turnover in tropical forests and is a strong predictor of tree mortality; yet, it is not typically represented in vegetation models. We incorporate crown damage into the Functionally Assembled Terrestrial Ecosystem Simulator (FATES), to evaluate how lags between damage and tree recovery or death alter demographic rates and patterns of carbon turnover. We represent crown damage as a reduction in a tree's crown area and leaf and branch biomass, and allow associated variation in the ratio of aboveground to belowground plant tissue. We compare simulations with crown damage to simulations with equivalent instant increases in mortality and benchmark results against data from Barro Colorado Island (BCI), Panama. In FATES, crown damage causes decreases in growth rates that match observations from BCI. Crown damage leads to increases in carbon starvation mortality in FATES, but only in configurations with high root respiration and decreases in carbon storage following damage. Crown damage also alters competitive dynamics, as plant functional types that can recover from crown damage outcompete those that cannot. This is a first exploration of the trade‐off between the additional complexity of the novel crown damage module and improved predictive capabilities. At BCI, a tropical forest that does not experience high levels of disturbance, both the crown damage simulations and simulations with equivalent increases in mortality does a reasonable job of capturing observations. The crown damage module provides functionality for exploring dynamics in forests with more extreme disturbances such as cyclones and for capturing the synergistic effects of disturbances that overlap in space and time.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

The pH Dependence of Niclosamide Solubility, Dissolution, and Morphology: Motivation for Potentially Universal Mucin-Penetrating Nasal and Throat Sprays for COVID19, its Variants and other Viral Infections - David Needham (Pharmaceutical Research, 2022)

Comprehensive single‐PCR 16S and 18S rRNA community analysis validated with mock communities, and estimation of sequencing bias against 18S - Yi‐Chun Yeh; Jesse McNichol; David M. Needham; Erin B. Fichot; Lyria Berdjeb; Jed A. Fuhrman (Environmental Microbiology, 2021)
Summary Universal primers for SSU rRNA genes allow profiling of natural communities by simultaneously amplifying templates from Bacteria, Archaea, and Eukaryota in a single PCR reaction. Despite the potential to show relative abundance for all rRNA genes, universal primers are rarely used, due to various concerns including amplicon length variation and its effect on bioinformatic pipelines. We thus developed 16S and 18S rRNA mock communities and a bioinformatic pipeline to validate this approach. Using these mocks, we show that universal primers (515Y/926R) outperformed eukaryote‐specific V4 primers in observed versus expected abundance correlations (slope = 0.88 vs. 0.67–0.79), and mock community members with single mismatches to the primer were strongly underestimated (threefold to eightfold). Using field samples, both primers yielded similar 18S beta‐diversity patterns (Mantel test, p

Establishment of Siamese Fighting Fish on the Adelaide River floodplain: the first serious invasive fish in the Northern Territory, Australia - Michael P. Hammer; Michelle N. Skarlatos Simoes; Evan W. Needham; David N. Wilson; Murray A. Barton; Dean Lonza (Biological Invasions, 2019)

Genome and epigenome of a novel marine Thaumarchaeota strain suggest viral infection, phosphorothioation DNA modification and multiple restriction systems - Nathan A. Ahlgren; Yangyang Chen; David M. Needham; Alma E. Parada; Rohan Sachdeva; Vickie Trinh; Ting Chen; Jed A. Fuhrman (Environmental Microbiology, 2017)
Summary Marine Thaumarchaeota are abundant ammonia‐oxidizers but have few representative laboratory‐cultured strains. We report the cultivation of Candidatus Nitrosomarinus catalina SPOT01, a novel strain that is less warm‐temperature tolerant than other cultivated Thaumarchaeota. Using metagenomic recruitment, strain SPOT01 comprises a major portion of Thaumarchaeota (4–54%) in temperate Pacific waters. Its complete 1.36 Mbp genome possesses several distinguishing features: putative phosphorothioation (PT) DNA modification genes; a region containing probable viral genes; and putative urea utilization genes. The PT modification genes and an adjacent putative restriction enzyme (RE) operon likely form a restriction modification (RM) system for defence from foreign DNA. PacBio sequencing showed >98% methylation at two motifs, and inferred PT guanine modification of 19% of possible TGCA sites. Metagenomic recruitment also reveals the putative virus region and PT modification and RE genes are present in 18–26%, 9–14% and

Every base matters: assessing small subunit rRNA primers for marine microbiomes with mock communities, time series and global field samples - Alma E. Parada; David M. Needham; Jed A. Fuhrman (Environmental Microbiology, 2016)
Summary Microbial community analysis via high‐throughput sequencing of amplified 16S rRNA genes is an essential microbiology tool. We found the popular primer pair 515F ( 515F‐C ) and 806R greatly underestimated (e.g. SAR 11) or overestimated (e.g. Gammaproteobacteria) common marine taxa. We evaluated marine samples and mock communities (containing 11 or 27 marine 16S clones), showing alternative primers 515F‐ Y (5′‐ GTG Y CAGCMGCCGCGGTAA ) and 926R (5′‐ CCGYCAATTYMTTTRAGTTT ) yield more accurate estimates of mock community abundances, produce longer amplicons that can differentiate taxa unresolvable with 515F‐C / 806R , and amplify eukaryotic 18S rRNA . Mock communities amplified with 515F‐Y / 926R yielded closer observed community composition versus expected (r 2 = 0.95) compared with 515F‐Y / 806R (r 2 ∼ 0.5). Unexpectedly, biases with 515F‐Y / 806R against SAR11 in field samples (∼4–10‐fold) were stronger than in mock communities (∼2‐fold). Correcting a mismatch to T haumarchaea in the 515F‐C increased their apparent abundance in field samples, but not as much as using 926R rather than 806R . With plankton samples rich in eukaryotic DNA (> 1 μm size fraction), 18S sequences averaged ∼17% of all sequences. A single mismatch can strongly bias amplification, but even perfectly matched primers can exhibit preferential amplification. We show that beyond in silico predictions, testing with mock communities and field samples is important in primer selection.

PLGA and PHBV Microsphere Formulations and Solid-State Characterization: Possible Implications for Local Delivery of Fusidic Acid for the Treatment and Prevention of Orthopaedic Infections - Chiming Yang; David Plackett; David Needham; Helen M. Burt (Pharmaceutical Research, 2009)

Dynamics of Neutrophil Membrane Compliance and Microstructure probed with a Micropipet-based Piconewton Force Transducer - Scott I. Simon; Tun Nyunt; Kathryn Florine-Casteel; Ken Ritchie; H. P. Ting-Beall; Evan Evans; David Needham (Annals of Biomedical Engineering, 2007)

Lysolipid exchange with lipid vesicle membranes - David Needham; Doncho V. Zhelev (Annals of Biomedical Engineering, 1995)